The American roommate experiment - Armas, Elena ([Spanish love deception, 2022)
"Rosie Graham has a problem. A few, actually. She just quit her well paid job to focus on her secret career as a romance writer. She hasn't told her family and now has terrible writer's block. Then, the ceiling of her New York apartment literally crumbles on her. Luckily she has her best friend Lina's spare key while she's out of town. But Rosie doesn't know that Lina has already lent her apartment to her cousin Lucas, who Rosie has been stalking--for lack of a better word--on Instagram for the last few months. Lucas seems intent on coming to her rescue like a Spanish knight in shining armor. Only this one strolls around the place in a towel, has a distracting grin, and an irresistible accent. Oh, and he cooks. Lucas offers to let Rosie stay with him, at least until she can find some affordable temporary housing. And then he proposes an outrageous experiment to bring back her literary muse and meet her deadline: He'll take her on a series of experimental dates meant to jump-start her romantic inspiration. Rosie has nothing to lose. Her silly, online crush is totally under control--but Lucas's time in New York has an expiration date, and six weeks may not be enough, for either her or her deadline."--